Holistic approach to R&D products' evaluation for commercialization under open innovations - Nataliya I. Chukhray; Oleksandra B. Mrykhina; Ivan Izonin (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
A holistic approach to R&D products' evaluation for commercialization under open innovations is developed. The approach is tested on the example of the device of the interferometric determination of the refractive index of crystalline materials in the optical range. The proposed approach will allow setting a price that will satisfy all the parties of a transfer agreement with a higher level of accuracy and will meet market requirements. Unlike popular methods of evaluating the R&D product, a holistic approach will, on the one hand, be based on the actual costs and the break-even level of a R&D product and, on the other hand, will determine how much the consumer is receptive to a R&D product, and, then again, will show how the added value of the product will develop under the influence of market effects. It is noted that the application of a holistic approach to R&D products' evaluation for commercialization should be supplemented by assessing the willingness of potential customers to purchase this R&D product at a specific price. It is proved that the proposed holistic approach to R&D products' evaluation for commercialization is multifunctional. The approach can be applied to different types of economic activity, R&D products, and types of markets. The obtained prices based on the application of a holistic approach to R&D products' evaluation for commercialization and the results of marketing research of the interferometry market testified to potential prospects of the commercialization of a R&D product of the interferometric determination of the refractive index of crystalline materials in the optical range and its long-term competitiveness. Based on the results, the key provisions of the concept of providing competitive benefits for the period of implementation of the analyzed R&D product are identified. Taking into account fundamental elements of the open innovation paradigm underpins the authors' holistic approach.
Keywords: 650; commercialization; evaluation; holistic approach; open innovations; R&D products